2016
DOI: 10.3389/fpsyg.2016.00670
|View full text |Cite
|
Sign up to set email alerts
|

A Reverse Stroop Task with Mouse Tracking

Abstract: In a reverse Stroop task, observers respond to the meaning of a color word irrespective of the color in which the word is printed—for example, the word red may be printed in the congruent color (red), an incongruent color (e.g., blue), or a neutral color (e.g., white). Although reading of color words in this task is often thought to be neither facilitated by congruent print colors nor interfered with incongruent print colors, this interference has been detected by using a response method that does not give any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Hence, in the last ten years, mouse-tracking flourished in many fields of psychological research (for a review, see Erb, 2018;Freeman, 2018;Freeman, Dale, & Farmer, 2011), finding applications in studies of phonological and semantic processing (Dale et al, 2007;Dshemuchadse, Grage, & Scherbaum, 2015;Spivey et al, 2005), cognitive control (Dignath, Pfister, Eder, Kiesel, & Kunde, 2014;Scherbaum, Dshemuchadse, Fischer, & Goschke, 2010;Yamamoto, Incera, & McLennan, 2016), selective attention (Frisch, Dshemuchadse, Görner, Goschke, & Scherbaum, 2015), numerical cognition (Szaszi, Palfi, Szollosi, Kieslich, & Aczel, 2018), perceptual choices (Quinton, Volpi, Barca, & Pezzulo, 2014), moral decisions (Koop, 2013), preferential choices (Koop & Johnson, 2013;O'Hora, Dale, Piiroinen, & Connolly, 2013), lexical decisions (Barca & Pezzulo, 2012, 2015, and value-based decisions (Calluso, Committeri, Pezzulo, Lepora, & Tosoni, 2015;Dshemuchadse et al, 2013;Kieslich & Hilbig, 2014;Koop & Johnson, 2011;O'Hora, Carey, Kervick, Crowley, & Dabrowski, 2016;Scherbaum et al, 2016;Scherbaum, Dshemuchadse, Leiberg, & Goschke, 2013;Scherbaum, Frisch, & Dshemuchadse, 2018b, 2018avan Rooij, Favela, Malone, & Richardson, 2013).…”
Section: Mouse-tracking As a Process-tracing Methodsmentioning
confidence: 99%
“…Hence, in the last ten years, mouse-tracking flourished in many fields of psychological research (for a review, see Erb, 2018;Freeman, 2018;Freeman, Dale, & Farmer, 2011), finding applications in studies of phonological and semantic processing (Dale et al, 2007;Dshemuchadse, Grage, & Scherbaum, 2015;Spivey et al, 2005), cognitive control (Dignath, Pfister, Eder, Kiesel, & Kunde, 2014;Scherbaum, Dshemuchadse, Fischer, & Goschke, 2010;Yamamoto, Incera, & McLennan, 2016), selective attention (Frisch, Dshemuchadse, Görner, Goschke, & Scherbaum, 2015), numerical cognition (Szaszi, Palfi, Szollosi, Kieslich, & Aczel, 2018), perceptual choices (Quinton, Volpi, Barca, & Pezzulo, 2014), moral decisions (Koop, 2013), preferential choices (Koop & Johnson, 2013;O'Hora, Dale, Piiroinen, & Connolly, 2013), lexical decisions (Barca & Pezzulo, 2012, 2015, and value-based decisions (Calluso, Committeri, Pezzulo, Lepora, & Tosoni, 2015;Dshemuchadse et al, 2013;Kieslich & Hilbig, 2014;Koop & Johnson, 2011;O'Hora, Carey, Kervick, Crowley, & Dabrowski, 2016;Scherbaum et al, 2016;Scherbaum, Dshemuchadse, Leiberg, & Goschke, 2013;Scherbaum, Frisch, & Dshemuchadse, 2018b, 2018avan Rooij, Favela, Malone, & Richardson, 2013).…”
Section: Mouse-tracking As a Process-tracing Methodsmentioning
confidence: 99%
“…The trained MLP was run repeatedly to generate the output time, which was determined when the accumulated output of one of the output vectors exceeded a response threshold. The system was able to reproduce the basic Stroop effect and predicted a reverse-Stroop effect that has been recently observhed [45].…”
Section: Computer Simulations Of the Stroop Effectmentioning
confidence: 86%
“…Instead, we performed 50 within-participants t -tests (one every 20 ms) for the first 1,000 ms of the mouse trajectories. To maintain the overall Type-I error rate below 0.05, we used Monte Carlo simulations to calculate the minimum threshold of contiguous t -tests that had to be significant in order to consider the effect real (for a detailed explanation of this approach, see Dale et al, 2007 ; Yamamoto et al, 2016 ). Using this threshold, we observed that interference emerged 420 ms after stimulus onset in the within-language condition and 500 ms after stimulus onset in the between-language condition, which led us to conclude that the difference is 80 ms.…”
Section: Suggestionsmentioning
confidence: 99%